Comparison of Two Control Programs of the VVER-1000 Nuclear Power Unit Using Regression Data Mining Models - Foshch, T.; Machado, J.; Portela, F.; Maksimov, M.; Maksimova, О. (Ядерна та радіаційна безпека, 2016)
A load-following mode of nuclear power plants (NPP) is a complicated procedure because there are significant changes in many interrelated processes. In order to show which control program (CP) of NPP is better to use, data mining (DM) techniques can be introduced. This study proposes a DM approach in order to show a possibility of using DM regression models for NPP. The datasets for DM were obtained by simulating two static CP of VVER-1000 NPP in Simulink software of Matlab program package.